Modelling the effects of production rates and physico-chemical parameters on pitting rate and pit depth growth of onshore oil and gas pipelines - Ossai, C.; Boswell, Brian; Davies, Ian (Maney Publishing, 2016)
© 2016 Institute of Materials, Minerals and Mining.To estimate the pitting rate of internally corroded oil and gas gathering pipelines, a multivariate regression modelling was carried out, using pitting rates and operating parameters. These operating parameters, temperature, pH, CO2 partial pressure, water cut, wall shear stress, chloride ion concentration, sulphate ion concentration, operating pressure, oil production rate, gas production rate and water production rate, were obtained from routine monitoring of the pipelines, whereas, the pitting rates (mean pit depths over time) were determined by the ultrasonic thickness measurement technique. The operating parameters and pitting rates were also used to estimate the pit depth growth of the pipelines using Monte Carlo simulation, and field data were used to test the developed models. The results obtained indicated that the pipelines under severe pitting corrosion rate were, more conservatively predicted than those under low, moderate and high pitting corrosion rates.